Competition and Innovation in Retail Electricity Markets: Evidence from Italy. (February 2017) - Stagnaro, Carlo
Abstract: Italy's 2015 Annual Competition Law, if finally approved, provides for phasing out retail electricity price regulation, as well as the implementation of full retail liberalisation, from 1 July 2018. This is a significant reform, not just because it is consistent with the broader market design for electricity. Indeed, retail liberalisation is a qualifying element of the full integration of the European Union's electricity market. The full opening of retail markets provides a great opportunity for innovation, both on the demand side and on the supply side. This article investigates the theoretical background, and presents some empirical evidence, on the competition–innovation nexus in retail electricity markets.